Age Estimation from the Rib by Phase analysis - An autopsy study in males (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Age is an extremely vital parameter in personal identity and its determination from skeletal remains has been studied and analyzed by many workers. In the present study the sternal end of fourth ribs were used for determination of age by direct observation. One of the great works on this subject was done by M.Yasar Iscan(1984) on white males. Over the years numerous tests have confirmed the reliability of this technique on varied samples from different population. Present study is an effort to test the application of the method developed by Yasar Iscan on a population in the state of Kerala. The sample consisted of fourth ribs on right side from 219 males of known age and race. The ribs were assigned to one of nine phases (0 through 8) based on changes noted at the coctochondral junction.Statistical analysis indicated that these changes were age related and applicable to the population of India also.
Keywords: Age estimation; sternal end of fourth rib